Simon Weil: Kebebasan dalam Dunia yang Deterministik - Guinadi, Vega; Mulchand, Mulchand; Suryadi, Suryadi; Tukiran, Martinus (Jurnal Filsafat Indonesia, 2024)
The concept of "freedom" in philosophy has many interpretations and variants depending on the framework of philosophical thought followed by its thinkers. In general, freedom refers to an individual's ability to act, think, and make decisions in the absence of unwanted restrictions or pressures. The problems of freedom and necessity (or determinism) are among the most widely debated philosophical problems. This problem arises in human history when people question whether their actions may be determined by factors unknown to them and beyond their control or power, so that human freedom is actually determined or limited. This article aims to examine and discuss the thought of Simone Weil, a 20th-century French Socialist philosopher and activist, who identifies three types of necessity that affect human freedom, in the context of this deterministic world and how men can become free in every kind of necessity. The method used in this study is literature review and analysis, with the aim of showing, through analysis of Weil's writings and philosophical thought, how Weil synthesizes the idea of freedom with acceptance of human limitations. The results show Simone Weil's unique view that presents a conception of freedom that involves awareness, responsibility, and self-transformation in a deterministic world.